THE CONTROLLED REVOLUTION. SPAIN AND MEXICO AT THE BEGINNING OF THE ERA OF THE PRONUNCIAMIENTOS(1820-1821) (Tzintzun, Revista de Estudios Históricos, 2024)
After several failed attempts at uprisings, unleashed after 1814 with the return ofFernando VII to his absolutist throne, in 1820 the liberal revolution wouldtriumph again at the hands of Rafael del Riego, and with this, not only would theconstitutional regime be reestablished, rather, the destinies of the overseaskingdoms would head towards their final break. The case of New Spain issignificant because a year later Agustín de Iturbide took the rieguista model toachieve independence from the Mexican Empire, instituting a new way ofnegotiation: the pronunciamiento, which would be present throughout theMexican 19th century.
Keywords: Hispanic Liberal Revolution; Sexenio absolutista; Trienio Liberal; New Spain Independence; Trigarante movement